Like a Lake - Mavor, Carol (Project Muse, 2020)
A vivid, imaginative response to the sensual and erotic in postwar American photography, with attention to the beauty of the nude, both male and female. When photographer Coda Gray befriends a family with a special interest in a young boy, the motivation behind his special attention is difficult to grasp,
10.1515/9780823289349
Keywords: Electronic books.; 1960s.; California.; Japanese Americans.; Photography.; childhood.; cuisine.; gay sexuality.; love.; maternal.; summer of love.; the child.; utopia.; water.; Photography; Mothers and sons